Cassava Root Chips as an Alternative Energy Feed Ingredient in Broiler Ration - Tesfaye , Etalem; Animut, Getachew; Urge, Mengistu; Dessie, Tadelle (International Journal of Poultry Science, 2013)
A total of 300 day-old Hubbard Classic broiler chicks with initial body weight (BW) of 43.6±1.33 (mean±SD) were randomly and equally distributed into 15 pens, representing five feeding treatments with three replication per treatment to evaluate the performance of chicks fed varying dietary levels of cassava root chips (CRC) replacing corn grain (CG). Treatments were replacement of CG with CRC at 0 (T1), 25 (T2), 50 (T3), 75 (T4) and 100% (T5) levels. Isocaloric and isonitrogenous starter and finisher rations were used. Four birds 2 from each sex were randomly taken from each replication and slaughtered for carcass evaluation at the end of the study. The metabolizable energy content of CRC and CG were 3852 and 3753 kcal/kg dry matter (DM), respectively. Daily DM intake during the entire experimental period ranged 61 to 67 g/bird and was greater (P<0.05) for T5 than T3 and T4, while values for T1 was similar with other treatments. Change in BW, daily BW gain and DM conversion efficiency were similar (P>0.05) among treatments. Replacement of CRC for CG at higher levels (75 and 100%) lowered (P<0.05) yield of most carcass parameters such as slaughter weight, dressed weight, eviscerated weight, breast weight, thigh weight, drumstick weight and giblet weight. The same carcass parameters were greater (P<0.05) for male than female birds but abdominal fat percentage was higher for females. In conclusion, based on DM intake and growth performance of broilers obtained in this study, CRC could completely replace corn grain in broiler diets as energy feed ingredient. However, looking on the results of yields of major carcass parameters, CRC should substitute corn grain not more than 50%.